Comparison of physicochemical properties of different tissues from China climbing perch Anabas testudineus and crucian carp Carassius auratus. Issue 3 (22nd January 2022) - Luo, Qiulan; Zha, Guangcai; Lin, Liyun; Huang, Yongping; Zou, Xianghui
Abstract: This study aimed to investigate nutrition in climbing perch Anabas testudineus which is an important nutritious economic freshwater fish in Asia and compare with Carassius auratus (crucian carp). Three kinds of tissues, including muscle, livers, and eggs, were isolated, respectively. Physicochemical properties including moisture, ash, protein, amino acids, fat, vitamins, and calcium contents in those tissues were determined. The results showed climbing perch muscle and liver contained less moisture, but more protein, amino acids, and vitamins than crucian carp muscle and liver. While moisture, ash, protein, and total amino acids contents of climbing perch egg were lower than those of crucian carp egg. Climbing perch egg had more fat, vitamins, and calcium than crucian carp egg. The amino acid profile was also performed, and 16 amino acids were identified and quantified in muscle, liver, and egg. Among tissues, the highest and lowest concentration of total amino acid content was found in crucian carp eggs and livers, respectively. Glutamic acid (Glu) and histidine (His) were the most and least amino acids in climbing perch and crucian carp tissues, respectively. Sixteen amino acids in climbing perch egg were less than those in crucian carp egg while it is an opposite case in muscle and liver, which amino acids of climbing perch tissues were more than those of crucian carp muscle and liver. Vitamin A of climbing perch was more than crucian carp in all three tissues, but vitamin E content in climbing perch liver was lower than that of crucian carp liver. Calcium content of muscle had no difference between two species. The abovementioned comparison of physicochemical properties of different tissues from China climbing perch and crucian carp will provide a necessary supplementary of freshwater muscle nutrition research, also was helpful for application of climbing perch. Abstract : Physicochemical properties of three kinds of tissues, including muscle, livers, and eggs from climbing perch and crucian carp were determined, respectively. The results showed climbing perch muscle and liver contained less moisture, but more protein, amino acids, and vitamins than crucian carp muscle and liver, while moisture, ash, protein, and total amino acids contents of climbing perch egg were lower than those of crucian carp egg. The comparison of nutrition of different tissues from China climbing perch and crucian carp was helpful for application of climbing perch.